1993
DOI: 10.1177/095632029300400204
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidate Derivatives of AZT as Inhibitors of HIV: Studies on the Carboxyl Terminus

Abstract: SummaryNovel phosphoramidate derivatives of the anti-HIV nucleoside analogue AZT have been prepared by phosphorochloridate chemistry. These materials carry carboxy-protected, arnlnor-aclds, and are designed to act as membrane-soluble prodrugs of the bio-active free nucleotides. In vitro evaluation revealed the compounds to have a pronounced, selective antiviral activity. In particular, variation in the carboxy terminus region is studied. For alkyl phosphates small changes in the structure of the amino ester le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The monoamidate prodrugs of the monophosphate of AZT exhibit minimal or no enhancement in in vitro anti-HIV activity (16,17). The modest in vitro effects seen with these AZT prodrugs have been explained in part by the lability of the AZT monophosphate bond, which can readily hydrolyze back to AZT.…”
Section: Discussionmentioning
confidence: 99%
“…The monoamidate prodrugs of the monophosphate of AZT exhibit minimal or no enhancement in in vitro anti-HIV activity (16,17). The modest in vitro effects seen with these AZT prodrugs have been explained in part by the lability of the AZT monophosphate bond, which can readily hydrolyze back to AZT.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the alaninyl carboxylate ester moiety of the trichloroethyl AZT-alaninyl phosphoramidate diester revealed that although increasing steric bulk of the ester group was associated with decreasing activity, changes in the ester did not signi®cantly affect the anti-HIV-1 activity in C8166. 131 Interestingly, p-bromo phenol alaninyl phosphoramidates of AZT have been shown to have potent spermicidal, as well as, anti-HIV-1 activity and may be useful as vaginal antiviral prophylactics. 146±149 Polyether para-substituted aryl phosphoramidates have also been constructed and shown to improve the water solubility of aryl amino acid phosphoramidates by 30-fold with little effect on antiviral potency.…”
Section: Phosphoramidate Diestersmentioning
confidence: 99%
“…The generality of the MMPA platform to other phenolic drugs with more complicated structures was investigated. Phosphonamidate prodrugs of phenolic drugs SN38 24 (14), estradiol 25 (16), and naloxone 26 (18) (Figure 4) were synthesized by using the same method as described for compounds 3−9 (Scheme 1). The pharmacokinetic profiles of compounds 15, 17, and 19, each as a mixture of its diastereoisomeric pair, were evaluated in beagle dogs via oral administration (Table 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous attempts to make 1 orally bioavailable through formulation and prodrug modifications have met with limited success. Our efforts turned to the aryloxyphosphon­amidate ProTide technology first reported by the McGuigan group, which was used subsequently by Gilead Sciences for the marketed drug tenofovir alafenamide . As illustrated with the prodrug of tenofovir ( A , Figure ), oral absorption is facilitated by the neutral phosphonamidate A of tenofovir with an amino acid ester and phenol.…”
Section: Introductionmentioning
confidence: 99%